PERILAKU MEMILIH PEMILIH PEMULA PUTUS SEKOLAH DALAM PEMILIHAN UMUM TAHUN 2019 DI KABUPATEN REMBANG (STUDI PADA JENJANG PENDIDIKAN SMP) - Devi - Maharani; Rina - Martini (Journal of Politic and Government Studies, 2021)
Beginner voters are citizens who are registered by the election organizer in the voter list, and just participating in the election to vote for the first time since the election was held in Indonesia with an age range of 17-21 years. Beginner voters who have just entered the age of their voting rights don’t have a broad political reach yet, which makes them very vulnerable to be influenced and approached by certain parties. Socialization about politics and elections is being given to the beginner voters, especially those at the senior high school education level, this has made voters who have dropped out of school at the previous education level not having the opportunity to get the socialization. Therefore this research will focus on finding out the voting behavior of the beginner voters who dropped out of school in the 2019 general election in Rembang Regency, especially at the junior high school level. This study uses a qualitative descriptive method to achieve the research objectives. The results showed that between the three approaches to voter behavior, the sociological approach, the psychological approach, and the rational approach, the informants tended to be prefer to rational approach. They choose the candidate of their choice by paying attention to the quality of the candidate and trying to choose a candidate who they think is better and more capable of becoming a leader and who will give benefits both for themselves and the country.